The financialization of everyday life (2020)
The term “financialization of daily life” was coined by Marxist sociologist Randy Martin in the identically titled book (Martin, 2002). The book’s main focus was growing indebtedness; however, since its publication, the terms “financialization of daily life” and “financialization of everyday life” have inspired studies looking at subjects ranging from everyday investment to pensions, insurance, and the financialization of biological life itself. As it is often the case with terms that become buzzwords overnight, the financialization of everyday life literature is informed by different conceptual uses, theoretical traditions, and critical angles. This chapter provides an overview of this dynamic field. The first part looks at what is the financialization of everyday life, contrasting three main uses of the term. The second part summarizes the socio-economic processes, associated with neoliberalism, that provide the common starting points of all approaches to the financialization of everyday life (FoEL thereafter). The third part, in turn, discusses the main theoretical traditions as part of which the FoEL has been studied: (1) Foucauldian governmentality approaches that undoubtedly had the biggest impact on the field; (2) (cultural) economic sociology in a Weberian and Zelizerian tradition, (3) social studies of finance; and (4) the sociological study of inequality. This part looks at the longer traditions as part of which FoEL arguments have been proposed in each area and maps the key debates. The fourth part discusses the critical angles used by each tradition. The chapter concludes by considering the ways in which the FoEL lens enables constructive criticism of contemporary finance.